Partial Recanalization of a Large Vessel Acute Ischemic Stroke With Intravenous Tissue Plasminogen Activator, Followed by Systemic Anticoagulation, in the Setting of COVID-19-Induced Hypercoagulability: A Case Report. (July 2021) - LaBarbera, Vincent A.; Azher, Aidan; Jayaraman, Mahesh V.; Wendell, Linda C.; Sacchetti, Daniel C.; Thompson, Bradford
We report on the use of systemic heparinization following thrombolysis with intravenous tissue plasminogen activator (t-PA) for acute ischemic large vessel stroke, in the setting of COVID-19-induced hypercoagulability, with partial recanalization of the internal carotid artery. Off-label systemic heparinization was used within 12 hours of t-PA administration, after extensive multidisciplinary collaboration and family discussion, given evidence of severe hypercoagulability. We conclude that thrombolysis should be considered for all eligible patients with suspected or confirmed COVID-19 and acute ischemic stroke, and systemic anticoagulation, although with inherent risks, may be a useful adjunct treatment modality in selected patients who have received intravenous thrombolysis.